Estrategias metodológicas para una convivencia armónica en el décimo año paralelo “A” en la Unidad Educativa Cristiana Nazareno, en el período académico 2021-2022. - Yumiseba Escudero, Mishell Yadira (2022)
The present research work analyzes two variables, the methodological strategies and harmonious coexistence, which could strengthen the practices of school in the tenth- year students of the Nazarene Christian Educational Unit. The main objective was to promote methodological strategies for a harmonious coexistence in the tenth year parallel A. It was derived from a qualitative-quantitative approach methodology, that is, there was an approach to study and interpret the phenomenon in a natural way, based on what was studied. It was carried out with a descriptive, correlational, exploratory and explanatory type of research; the data collection techniques in the research was the observation sheet for the students, with a population of 35 students aged 11 to 12 years. Which I present results of the methodological strategies evidencing that 43% the socializing strategy allows them to live with people around them, in addition to sharing experiences, and controlling their emotions; by harmonious coexistence. In the results obtained, 60% of the students have always been tolerant in the classroom. Concluding that the methodological strategies are of great importance in basic education, since the students comprehensively developed the strengthening of skills, promoting principles, the values that guide better behavior and decision making in daily activities either in the labor, social or family environment, the teacher must be permanently trained in order to implement innovative strategies according to the needs and interests of the students in the teaching-learning process.